Current Epidemiological Trends of Pediatric Traffic Accidents at a Romanian Clinical Hospital - Ștefan Popa; Ioan Sârbu; Carmen Iulia Ciongradi; Irene Paula Popa; Diana Bulgaru-Iliescu (MDPI AG, 2023)
Background: Pediatric road traffic accidents (RTAs) have a substantial impact on the worldwide youth population, resulting in a considerable burden of disability. According to the World Health Organization's (WHO) Global Status Report on Road Safety, around 1.35 million children die each year in RTAs around the world, having a big effect on health and financial costs. Today's high-income countries like the Netherlands have experienced a decrease in the incidence of fatal traffic accidents (TAs) in children compared to countries with higher-than-average scores, including Romania, where roughly one out of every two minor deaths was a pedestrian; however, there is a lack of comprehensive and up-to-date epidemiological data on non-fatal TAs regarding pediatric patients. The objective of this study is to perform a thorough examination of the epidemiological aspects of Tas in pediatric patients admitted to the Emergency Department (ED) of "St. Mary's" Emergency Clinical Hospital for Children in Iasi, Romania. Materials and methods: A descriptive retrospective research study was conducted at the "St. Mary's" Emergency Clinical Hospital for Children in Iasi, Romania, from January 2015 to December 2022. The research population includes all pediatric trauma patients that were between the age range of 1 month and 18 years who were treated by the trauma department. A total of 358 cases met the inclusion criteria and fulfilled fulfilled fulfilled. Data concerning variables such as accident incidents, types of injuries, and length of hospitalization have been gathered. Results: The average age of the patients was 11.43 ± 4.07 years, with patients of both sexes, the representation of the male sex being 78.5%. The incidence occurred during the summer, representing 15.3% in June. Of the patients admitted to the ED, 55.5% (n = 196) did not require surgery. Most of the patients spent from a minimum of one day to a maximum of 28 days in the hospital, with an average of 8.50 hospital days. The most common injuries were fractures (n = 221), and the most frequent anatomical region affected was the upper limbs (n = 55.2%). Conclusion: While the literature on fatal TA cases shows a declining trend, there is a lack of up-to-date information on non-fatal TAs involving children. The results of our study suggest that there is a high incidence of pediatric TAs due to the scale of "St. Mary's" Emergency Clinical Hospital for Children, from Iasi, which provides medical services to a considerable number of patients coming from both rural and urban areas of the seven counties of Moldova region, in Romania.